Academic Pressure and Health Habit Formation Among Scholars: Basis For Community Health Teaching - Bernal Jr., Hernando L.; Gumaru, Renz Chester R.; Go, Bernie B. (Randwick International of Education and Linguistics Science Journal, 2024)
This study aimed to evaluate the level of academic pressure experienced by university scholars in the Philippines across five dimensions: self-expectation, workload, despondency, study-related pressure, and worry about grades. Additionally, it examined the scholars' formation of health habits in six areas: water intake, rest, physical activity, nutrition/diet, temperance, and overall physical condition. The study also explored the relationship between academic pressure and health habits. Findings revealed that the scholars experienced a relatively high level of academic pressure, with self-expectation emerging as the most significant source. Conversely, the scholars exhibited a low level of healthy practices, particularly in the area of rest, which was identified as the least practiced health habit. On a positive note, temperance was highlighted as the most favorable health behavior, reflecting the scholars' ability to exercise moderation.